Moyamoya Disease Explored Through RNF213 Genetics, Molecular Pathology, and Clinical Sciences - Koizumi, Akio.; Nagata, Kazuhiro; Houkin, Kiyohiro; Tominaga, Teiji; Miyamoto, Susumu; Kure, Shigeo; Tournier-Lasserve, Elizabeth; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book presents the latest findings on biological, epidemiological, and clinical investigations of RNF213, which is thought to be involved in many biological processes and plays a key role in cerebro- and cardiovascular disease . By discussing the epidemiology and genetic epidemiology of the disease with a particular focus on the molecular function of RNF213, research using animal models, diagnosis, therapy and clinical management around the world, this work makes a valuable contribution to the study of the disease. Moyamoya Disease Explored Through RNF213 is an indispensable resource for both beginning and experienced researchers, pediatricians, neurologists, and neurosurgeons who are seeking comprehensive information on adult and childhood stroke.
Part I: Prologue -- 1. A prologue to moyamoya disease and RNF213 -- 2. Concept of moyamoya Disease -- Part II: Genetic Epidemiology -- 3. Molecular Epidemiology in East Asian Countries and in the World -- Part III: Biochemistry, Function and Molecular Pathology -- 4. Molecular Biology of Mysterin/RNF213 -- 5. Physiological Role of Mysterin/RNF213 in Zebrafish -- 6. Pathological Investigation on RNF213: Animal Models Knockout and Transgenic Mice in Diabetes and Signal Transduction -- 7. Pathological Investigation on RNF213: Animal Models of Rnf213-knockout and Knock-in Mice -- 8. RNF213 and Circulating Factors in Patients with Moyamoya Disease -- 9. Genetics of Moyamoya beyond RNF213. Monogenic Moyamoya Syndromes -- Part IV: Clinical Management 10. Natural History and Long-term Clinical Outcome after Conservative and Surgical Management -- 11. Significance of RNF213 in Clinical Management in Japan -- 12. Significance of RNF213 in Clinical Management in China -- 13. The Different Forms of Moyamoya Disease and Their Clinical Management -- 14. Vascular Diseases Attributable to RNF213 Other than Moyamoya Disease -- Part V: Epilogue -- Future Clinical Perspectives on RNF213 in Moyamoya Disease.
Keywords: Medicine; Public health; Neurology; Neurosurgery; Medicine & Public Health; Neurology; Neurosurgery; Public health